2018
DOI: 10.3390/nu10081069
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Irradiation of Skin Alters the Faecal Microbiome Independently of Vitamin D in Mice

Abstract: Reduced sunlight exposure has been associated with an increased incidence of Crohn’s disease and ulcerative colitis. The effect of ultraviolet radiation (UVR) on the faecal microbiome and susceptibility to colitis has not been explored. C57Bl/6 female mice were fed three different vitamin D-containing diets for 24 days before half of the mice in each group were UV-irradiated (1 kJ/m2) for each of four days, followed by twice-weekly irradiation of shaved dorsal skin for 35 days. Faecal DNA was extracted and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 50 publications
(59 reference statements)
1
26
1
Order By: Relevance
“…Because leg skin becoming thick during the later phase of the laying cycle might block most of the UV rays, we hypothesized that the intensity of the UVB-LED lamp may also be a major factor. UV (250-360 nm) was an effective method of acquiring vitamin D [34]. However, the results show that the serum 1,25(OH) 2 D 3 content was not affected by UVB exposure.…”
Section: Discussionmentioning
confidence: 92%
“…Because leg skin becoming thick during the later phase of the laying cycle might block most of the UV rays, we hypothesized that the intensity of the UVB-LED lamp may also be a major factor. UV (250-360 nm) was an effective method of acquiring vitamin D [34]. However, the results show that the serum 1,25(OH) 2 D 3 content was not affected by UVB exposure.…”
Section: Discussionmentioning
confidence: 92%
“…It is known that the disruption in the balance between regulatory and proinflammatory pathways of the immune system, as well as a compromise in the epithelial barrier integrity, is the basis for the pathogenesis of IBD, thus underlying the importance and the potential role of vitamin D in this disorder. Vitamin D exerts other important effects on intestinal microbiome [34,35], and further research is needed to better elucidate this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of the fecal microbiome may be another mechanism through which vitamin D influences the risk of developing IBD, as shown by preliminary studies in rat models [34]. In a small interventional study, Schäffler et al found that, in contrast to healthy controls, the administration of vitamin D to patients with CD was associated with changes in bacterial intestinal flora, which are particularly evident after one week: the typical bacteria shifted from Betaproteobacteria to Bacteroidetes [35].…”
Section: Vitamin D and Immune Functionmentioning
confidence: 99%
“…This points out that there is likely a time-of-day effect when sampling the microbiome [55]. Different types of light exposure can have an effect; mice exposed to UV irradiation showed a skewing of the microbiome towards increased Firmicutes: Bacteroidetes ratio [56]. Furthermore, Circadian disruption can alter the gut microbiome [57] and sensitivity to antitumor therapies [58].…”
Section: The Composition Of the Gut Microbiome Is Influenced By Many mentioning
confidence: 99%